Gene Signatures and Cancer-Immune Phenotypes Based on m6A Regulators in Breast Cancer - Zhao, Guanghui; An, Junhua; Pu, Qian; Geng, Wenwen; Song, Haiyun; Zhao, Qianqian; Gao, Haidong (Frontiers in Oncology, 2021)
The N6-methyladenosine (m6A) has been considered as a new layer of epitranscriptomic regulation on mRNA processing, stability and translation. However, potential roles of m6A RNA methylation modification in tumor immune microenvironment (TIME) of breast cancer are yet fully understood. In this study, we comprehensively evaluated the genetic variations and transcript expressions of 15 m6A regulators in 1,079 breast cancer samples from The Cancer Genome Atlas (TCGA) database. We validated major regulators had significantly differential mRNA and protein expression in tumor tissue compared to normal tissue from 39 pairs of clinical breast cancer samples with different molecular subtypes, and especially high expression of m6A readers YTHDF1 and YTHDF3 predicted poor survival. Two clusters of breast cancer patients identified by the 15 m6A regulators’ pattern showed distinct overall survival, immune activation status and immune cell infiltration, and clinical samples confirmed the diversity of lymphocytic infiltration. The profiles of these two clusters accorded with that of two classical cancer-immune phenotypes, immune-excluded and immune-inflamed phenotypes, it suggested that m6A regulators-based patterns might serve as crucial mediators of TIME in breast cancer. Moreover, the m6A phenotype-related gene signatures could also be survival predictor in breast cancer. Therefore, comprehensive evaluation of tumor m6A modification pattern will contribute to enhance our understanding of the characterization of immune cell infiltration in the tumor microenvironment and promote the responsiveness of breast cancer to immunotherapy.